Aktivisme Advokasi Amnesty International dalam Menghilangkan Praktik Perbudakan Modern di Qatar: Studi Kasus “Hidden Crime” dibalik Persiapan Piala Dunia 2022 - Dian Hapsari; Ika Riswanti Putranti; Marten Hanura (Journal of International Relations, 2022)
The election of Qatar as the host of the 2022 World Cup is enough to seize theattentionof the international community, because this world-class event is notonly the most awaited momentum by football lovers around the world but alsohelp strengthen relations between countries. However, as if escaped from publicview, in fact there is a hidden crime behind the preparation of the event which can be categorized as a form of modern slavery.This was allegedly based on thekafala system, which is a recruitment system for migrant workers that tends to be exploitative and much to the detriment of workers' rights such as low wages orhigh working hours.Thecase was revealedonthebasisofAmnesty International's investigation as an internationalnon-governmental organization engaged inHuman Rights. Through these findings, making the Qatari government as the event facilitator who was considered negligent in fulfilling the protection of laborrights, especially migrant workers, carried out policy reforms and transformation of its labor laws.Thus, Amnesty International's advocacy in influencing the policies and attitudes of the Qatari government can be said to be successful,although not yet comprehensive. This study aims to explain how the influence of Amnesty International is related to changes in Qatar policy in response to modernslavery.To answer the problems and research objectives, this research uses the concept of advocacy, the Advocacy Coalition Framework (ACF), NGOs, and modern slavery with qualitative methods and data collection techniques through literature studies. This research shows that the advocacy carried out by Amnesty International was able to have implications for changing the attitude of the Qatari government in responding to the issue of modern slavery in its country, namely through policy changes regarding migrant workers, which in turn contributed to a number of positive impacts on the standard of living of migrant workers in Qatar.